Supraceliac Aortic Mural Thrombus Presenting with Peripheral or Mesenteric Acute Ischemia: A Scoping Review and Case Series - Bricilla Gnana Preethe; Jithin Jagan Sebastian; Sairam Subramanian (Indian Journal of Vascular and Endovascular Surgery)
Primary aortic mural thrombus (PAMT) leads to visceral and lower limb embolism in patients. The etiology of PAMT is usually idiopathic. Supra-celiac aortic mural thrombus (SCAT) has been thought to have a different etiological basis compared to PAMT. Treatment methods vary from anticoagulation to endovascular to surgical. We review here the available evidence on SCAT and describe our experience in three cases presenting with embolisms. A scoping review of PubMed was undertaken using a predefined definition of SCAT. Ten articles comprising 13 cases of SCAT presenting with visceral or peripheral embolism were identified and reviewed. Three patients with SCAT presenting to our institution are described. The first patient was a 50-year-old lady with no comorbidities who presented with a pedunculated aortic thrombus in the supra-celiac region with complete celiac artery thrombosis and embolism into superior mesenteric artery (SMA). She presented with extensive bowel gangrene and was palliated. The second patient, a 39-year-old diabetic lady with a similar presentation, came with near total thrombotic occlusion of the juxta celiac aorta with thrombus extending into the celiac artery and SMA. She underwent a trapdoor aortotomy, aortic thrombectomy with SMA embolectomy, and bowel management after which she recovered. The third was a 79-year-old hypertensive woman with celiac artery compression and thrombotic occlusion with extension of thrombus as a pedunculated SCAT. She presented with popliteal artery embolism and was treated by popliteal thrombectomy with conservative management for the aorta. She recovered well and has been asymptomatic since. SCAT is a rare entity that occurs possibly due to median arcuate ligament compression and high aortic wall shear stress in the vicinity, leading to high rates of embolisms. A high index of suspicion and early intervention will benefit this patient cohort. This condition has a high mortality rate if not identified and treated early. The goal of treatment is to avoid end-organ ischemia.